Cryopreservation of fish germ cells. Thematic bibliography - Ir. Hrytsyniak; T. Shvets (Ribogospodarsʹka Nauka Ukraïni, 2018)
Purpose. Forming a thematic bibliographic list of publications on studies of low-temperature preservation of sexual cells of various fish families and species and creating gene banks in order to preserve the genetic diversity of endangered fish species populations.